Respuesta :
Answer:
x = -17
Step-by-step explanation:
6 (x+4) = 4x -10 (given)
6x + 24 = 4x - 10 (distributive property of equality)
2x = -34 (subtraction property of equality)
x = -17 (division property of equality)
Ace Carlos
Answer:
x = -17
Step-by-step explanation:
First, distribute.
6 (x+4) becomes 6x + 24.
The new equation is : 6x + 24 = 4x - 10
Then, move all constants to one side, and all the x values to the other.
Add 10 to both sides, and subtract 6x from both sides, you get:
34 = -2x
Divide by -2x on both sides.
x = -17